Swearwords Used by Gangsters in the “Alpha Dog” Movie - Daniel Christian; Samuel Gunawan (Kata Kita: Journal of Language, Literature, and Teaching, 2014)
Many people assume that swearwords is a rude word and should be avoided. Those words are used to insult, to curse, to offend or to mock at something when the speaker has strong emotion (Hughes, 1991,05). To swear at someone or something is to insult and deprecate the object of abuse, as well as to use other kinds of dysphemism (Allan & Burridge, 2006,76). Apparently some experts and scholars have been able to prove that swearwords also has a purpose and a meaning beside the one as commonly held. Therefore, the writer took the "Alpha Dog" movie as an example of the analyzed cases. Examples have been found by the writer including the categories of epithets derived from tabooed bodily organs, epithets derived from bodily effluvia, epithets derived from sexual behaviours, dysphemistic epithets that pick on real physical characteristics that are treated as though they are abnormalities, imprecations and epithets invoking mental subnormality or derangement. Finally, the writer also managed to find a purpose or a reason for the people to use swearwords in real life.